Contest coefficients of the elite judo athletes of Russia and Kyrgyzstan (less than 60 kg, 66 kg, 73 kg and 81 kg) from 2010 till 2015 - Osipov, A.; Kudryavtsev, M.; Koptev, O.; Iermakov, S.; Bliznevskaya, V. (International Journal of Applied Exercise Physiology, 2018)
Study aim. The specialists note that the latest changes in the rules of judo have a negative impact on the quality of competition between the athletes representing the Russian Federation and the CIS countries. In connection with this the goal of the research was to search for the objective and informative criteria for assessing the level of preparedness of the judoists in Russia and Kyrgyzstan for conducting competitive fights. Another purpose of the research was to analyze the readiness level of the elite judo athletes from Russia and Kyrgyzstan to conduct competitive attacking fight in conditions with the significant changes of the rules of judo competitions based on the selected criteria.